Perceptions of racial discrimination and parenting reactions. The case of mixed Sub-Saharan African-Italian families in northern Italy - (:unkn) unknown (My University, 2021)
Over the past few decades, Italian society has become both multicultural and multi-ethnic, and its immigrant population is one of the most diversified in Europe (Blangiardo & Ortensi, 2020). In this context, the number of mixed families and mixed-parentage children has multiplied since the early 1990s. The wide diversity in country of origin of non-native spouses in mixed couples reflects the multitude of communities currently present in Italy. Among these, families where one spouse is from Sub-Saharan Africa are a minority. Although immigrants from this African region are not the largest group, they are one of the ethnic minorities with greater visibility in public discourse. In the eyes of many Italians, immigrants are mostly associated with African origins, 1 the Islamic religion and blackness, and their number is overestimated (Clini, 2015; Eurispes, 2019). In the postcolonial Italian context (Lombardi-Diop & Romeo, 2012), where prejudices and stereotypes linked to skin colour and African origins are particularly entrenched, and where multiethnicity is a relatively recent phenomenon, African-Italian families' experiences of racial discrimination is of particular interest, especially with regard to the parenting challenges associated with social integration among mixedparentage children (Lajus, 2018; 2019). During these families' socialization processes, it is crucial to know the connections between discrimination and socioeconomic status, gender and phenotypic diversity. At present, even if social representations of skin colour is an emerging issue with regard to the construction of identity in African-Italian children
Keywords: African Research